Functional identification of a putative stachyose synthase (StaS, Medtr7g106910.1) from Medicago truncatula, by overexpression in the Arabidopsis stachyose deficient double mutant atrs4/atrs5 - Hugo, Melt (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.